Venture team membership dynamics and new venture innovation - Fox, Brian C.; Simsek, Zeki; Heavey, Ciaran (Strategic Entrepreneurship Journal, 2023)
Abstract Research Summary Although pre‐entry startup experience is widely recognized as a driver of innovation in new ventures, a core feature of new venture teams is that their membership is fluid. In this article, we theorize and test whether venture team membership fluidity incrementally explains new venture innovation. We also investigate and demonstrate that team fluidity conditions the impact of pre‐entry startup experience present at founding. Testing our hypotheses with a cohort of 440 new ventures tracked for 8 years, we find support for the model across a wide range of specifications. Our study advances current understanding of the relationship between pre‐entry experience and new venture innovation, as well as novel insights into the central but often overlooked role of team fluidity. Managerial Summary New ventures rely on innovations to establish a market presence and compete against established firms. Even though team members are an essential source of inspiration, ideas, and resources to foster innovation, teams often change substantially as the venture evolves. We ask the question—does modifying the make‐up of the team make it more likely that the venture can innovate? We contend that such change significantly shapes the cognitive and interpersonal processes by which team members contribute to innovations. Our results suggest that new ventures undergoing member change can boost innovation in three ways: adding new members to the team with relevant experiences, taking advantage of opportunities to pause and reflect upon team processes in the wake of change, and mitigating the disruptive effects of change.